Local management of the COVID-19 pandemic in Norway: a longitudinal interview study of municipality chief medical officers - Silje Rebekka Heltveit-Olsen; Lene Lunde; Anja Maria Brænd; Ivan Spehar; Sigurd Høye; Ingmarie Skoglund; Pär-Daniel Sundvall; Guro Haugen Fossum; Jørund Straand; Mette Bech Risør (Taylor & Francis Group, 2024)
AbstractObjective To explore the experiences and views of Norwegian Municipality Chief Medical Officers (MCMOs) on preparedness, collaboration, and organization during the COVID-19 pandemic to gain insight into local crisis management of value for future pandemic responses.Design Longitudinal qualitative interview study. We conducted semi-structured digital interviews with nine MCMOs working in different municipalities in Norway from September to December 2020. Five MCMOs were re-interviewed from January to April 2021. We used thematic analysis to analyze the data.Results Through the analysis, three major themes were identified in the material; 1) The view of preparedness changed from being low-priority and dormant to the desire to strengthen preparedness as a permanent measure; 2) The nature of the pandemic forced a change in internal and external communication and collaboration for the MCMOs towards direct dialogue, teamwork and digital networking; 3) The pandemic changed the role and position of the MCMO within the municipal organization. Although most MCMOs were given a leading role in the municipal pandemic response, some MCMOs experienced that they were not positioned to fully exercise their intended role. In our material, de-authorization of the MCMO role seemed to coincide with the increasing size and organizational complexity of the municipality.Conclusions The Norwegian pandemic response and outcome have been regarded as successful internationally. Although the MCMOs managed to implement flexible and quick responses facilitated by teamwork, dialogue, and joint sensemaking, they also identified several challenges and shortcomings of the Norwegian pandemic preparedness requiring organizational and financial changes to sustain future health system resilience.